DESAINER TOYS SEBAGAI IDENTITAS GAYA HIDUP URBAN - Priyantoro, Eko (Visualita Jurnal Online Desain Komunikasi Visual, 2018)
Urban area is known by higher population density and vast human type in comparison to the areas surrounding it. Quick progression of Â lifestyle in urban has created new variant of culture. This condition become complex discourse of urban communities. In modern culture, all phenomena that happen in urban area become the heart of trend center. Supported by high achievement in technology, new trend which happen on urban area easily spreading to rural settlements. It cause evolution in so many aspects, includingÂ  of people behaviour or cultural. Toys is one of many aspect influenced by urban culture. â€œDesigner Toyâ€ is the kind of product which born in urban culture. This type of toys first appeared in late 1990s and are still in production today. There is tend of many various type of Designer Toys causing by highly market demand and toy lovers awareness. According through this research, writer has concluded that Designer Toys is the one of the most popular stuff from the urban culture. Although it just a newly genre of toys, the innovation growing too fast compare to other kind of toys.